Building capacities in a country of limited opportunities: experiences in teleworking of a group of young people from popular areas of Barquisimeto, Venezuela (Mayéutica Revista Científica de Humanidades y Artes, 2022)
In a connected world, Internet access is not a luxury, it is a necessity. More than four billion Internet users are searching for information, communication, recreation, education and work every day. This medium has become an important exercise of Human Rights, as it is used as an instrument to facilitate and expand freedoms conceived as capabilities, which allow people to do and be what they have reason to value. Under this sense, the objective of this research was to understand the experiences of three teleworkers located in the peripheral area of Barquisimeto, Lara state, related to the conditions of access in the pre and post pandemic context, considering its link with freedoms and Human Development. It consists of five chapters and is framed within the qualitative paradigm, specifically based on the phenomenological method. The technique used was the semistructured interview, which allowed for an analysis and interpretation of the information, making use of categorisation to investigate the experiences. The findings focus on the conditions of access to the Internet for young people in their sectors, and the obstacles that interfere with democracy, economic services, quality of life and, therefore, human development.
Keywords: freedoms; Internet access; teleworking; human development